Vaderskap in die Pauliniese korpus volgens 1 Korintiërs - Malan, F. S. (HTS teologiese studies, 2005)
Fatherhood in the Pauline corpus according to 1 CorinthiansThe word pathvr appears five times in 1 Corinthians: three times referring to God (1:3; 8:6; 15:24), once to Paul (4:15), once to Israel in the desert (10:1), and once to a physical father (5:1). Paul’s idea of fatherhood are his Jewish background, his view of the Greek and Roman conception of fatherhood, and his interpretation of the Old Testament understanding thereof. These images and Paul’s subtle differences from them are explored. Paul’s idea of fatherhood arises from his faith in God’s relationship with Jesus, and, through the crucified and risen Christ, with the congregation and the whole creation. Paul’s own humble life portrays Christ’s humiliation and the Father’s grace.